A Preliminary Taxonomic Study on the Flora of Rangpur District, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2021)
This study demonstrates that the vascular flora of the Rangpur district area consists of 825 species under 537 genera and 139 families. The pteridophytes and gymnosperms are represented by 25 and seven species, respectively, whereas the angiosperms by 793 species including 582 species of dicotyledons (Magnoliopsida) and 211 species of monocotyledons (Liliopsida). Poaceae with 67 species, representing 8.12% of the flora, is appeared as the largest family, and followed by Asteraceae, Fabaceae, Araceae, Malvaceae and Euphorbiaceae that collectively constitute 17.94% of this flora. Persicaria comprising 10 species is recorded as the largest genus, and followed by Ficus, Euphorbia, Solanum, Albizia and Brassica. About 59.71% taxa of this flora are herbs, 21.71% trees, 14.72% shrubs and the rest are palms, lianas, and bamboos. Erect herbs forming 35.22% of the flora comprise the most common life-form. In this flora, almost 64.29% taxa are native and the rest 35.71% are exotic. Nearly 62.61% taxa of the flora are found in wild, 26.90% as planted and 10.49% as cultivated. About 35.46% of the species commonly occur throughout all upazilas of this district. Most of the species are harboured in fallow lands, roadsides, gardens, and homesteads. All species of this district flora are known as economically useful. Most of its habitats and ecosystems are exposed to different threats. Adequate measures with effective management plans should be adopted and implemented for the sustainable use, improvement and conservation of this precious flora.Bangladesh J. Plant Taxon. 28(2): 329-365, 2021 (December)